Wola w psychosyntezie = Will and psychosynthesis - Białek, Ewa (Zielona Góra: Uniwersytet Zielonogórski)
Will is the most precious function inherent in man and yet it is the one that has been neglectedmost, both in family and school education. It is, therefore a matter of urgency to encourageand help the people to train and develop their will as a means to eliminate the lack of balance between the outer and the inner powers of men, introducing self-discipline, life purpose, protecting against their aggression of other uncontrolled drives.
Keywords: wola; psychosynteza